Time Domain Analysis of Electric Field on Wind Turbine Blade Under Salty Condition - Wahdain, Samer Saeed Sahel; Amir Izzani, Mohamed; Mohd Mawardi, Saari; Mohd Herwan, Sulaiman; MRM, Esa; ZA, Noorden (UTeM Press, 2023)
A wind turbine is a structure that converts the energy generated by the wind into electrical power by utilizing wind vans called wind blades. Thus, wind blades play an essential role in a wind turbine. Due to open and high terrain construction, wind turbines are continuously exposed to lightning strikes. Therefore, electrical field activity may vary during thunderstorms. Finite Element Method software with computational simulation and analysis was carried out to gain insight into the behavior of this electric field for wind turbine blades under different humidity conditions. Simulated module excitation and parameter based on natural occurrence will be implemented, and the findings of the results can be used in technological advancement.